Nanostructure of Red Blood Cell Membranes in Premature Neonates with Respiratory Distress Syndrome - S. A. Perepelitsa; S. V Alekseeva; V. A. Sergunova; O. E. Gudkova (Общая реаниматология)
Objective: to study the nanostructure of red blood cell membranes in premature babies with neonatal respiratory distress syndrome (NRDS), by applying atomic force microscopy. Subjects and methods. The investigation included 27 newborn infants, of them 13 premature babies with NRDS formed a study group. The mean gestational age was 33.1±2.3 weeks; their birth weight was 1800±299.3 g. A comparison group consisted of 14 full-term babies with favorable pregnancy and term labor. The mean gestational age of the babies was 39.4±0.5 weeks; their birth weight was 3131.7±588.8 g; the infants had a one minute Apgar score of 8±0.4. Their red blood cells were examined using an atomic force microscope. The objects to be examined were residual umbilical cord blood (RUCB) from the premature infants; central venous blood after 7 hours of birth and neonatal venous blood taken on day 7 of life. Results. RUCB from full-term babies contained planocytes that were a major morphological type of red blood cells. In physiological pregnancy and acute fetal hypoxia, the morphological composition of red blood cells in premature neonates with NRDS was close to that in full-term babies. The planocytes are also a major morphological type of red blood cells in the premature infants; the frequency of their occurrence varies. Stomatocytes are typical of all the neonates in the NRDS group; their frequency levels vary greatly: from 8 to 65% of the total number of erythrocytes. The examination revealed that the premature infants of 31—36 weeks gestation were characterized by abnormal erythrocyte shapes that showed a high variability. At birth, the premature babies were found to have changes in the nanostructure of red blood cell membranes, which were influenced by intrauterine hypoxia. The first-order value reflecting flickering in the red blood cell membrane varies to the most extent. Conclusion. Atomic force microscopy showed that the greatest changes in the structure of red blood cell membranes were found in RUCB. The premature babies with NRDS had intrauterine poikilocytosis caused by unfavorable factors, as confirmed by the presence of multiple correlations. Analysis of the nanostructure of red blood cell membranes revealed that the first-order value reflecting flickering in the red blood cell membrane was most sensitive; this indicator showed a slow normalization. Correspondence to: Key words: red blood cell membrane, nanostructure, planocytes, stomatocytes, premature newborn infants, respiratory distress syndrome.